A CASE STUDY OF SELF-DIRECTED LEARNING USING MOVIE TO PROMOTE ORAL COMMUNICATION - Mohammad Amro Mohammad Suleiman; Mahendran Maniam (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2019)
The main aim of this study is to help EFL students’ improve their oral communication proficiency out-of-class. To achieve that, video-movie was chosen as a medium for improving the subjects' oral communication proficiency. It was hoped that movie could function as a pseudo-immersion for the students, an accessible and easy alternative to being in the English native countries. Based on that, this study aim has been transformed into this research question ‘what effect does self-directed learning using movies has on the students' perceived oral communication proficiency?’. To answer that, six first year students at the faculty of English language and literature, Ajloun University in Jordan, were selected based on purposive sampling and divided equally into two groups, treatment and control, based on random assignment. The subjects in both groups were asked to take the self-assessment language test twice, once before the beginning of the case study scheme and another after. Likewise, to be interviewed twice, and to fill in the study notes during the case study scheme. Only the treatment group were given eight movies with its guides and asked to self-study with it over eight weeks. The results from the case study indicated that movie could help improve the students' oral communication proficiency with higher post-test scores than pre-test scores. Methodological triangulation from both the interviews and study notes also supports the assertion that movie improved the subjects’ oral communication proficiency. The subjects in the treatment group revealed in the post-interview that movies helped improve their listening skills and two subjects suggested that it could possibly have helped improve their speaking skills as well. Their perception in their study notes also supports the results. In conclusion, it is very likely that self-directed learning using movies has improved the students’ oral communication proficiency. This study has implications for practical applications in language teaching and learning which suggests that movie can be effective out of class. In addition, the results suggest that further larger scale investigations into students' language improvement out of class will be worth carrying out.